Antropolingwistyka dzisiaj: wyniki i perspektywy - Zaniewski, Jan; Griniev-Griniewicz, Sergiusz; Nizhneva, Natallia (Scripta Neophilologica Posnaniensia, 2018)
Antropolingwistyka dzisiaj: wyniki i perspektywy